Implementation of Environmental Health Service Policy at Kalimas Health Center Based on Minister of Health Regulation No. 13 of 2015 - Saputro, Dwi; Yuniarti, Yuniarti; Nugraheni, Dewi (Pena Medika : Jurnal Kesehatan, 2025)
The healthy environment program aims to realize a healthier environmental quality through the development of a regional health system in encouraging the development of a health-oriented sector to support promotive and preventive services in overcoming environmental-based diseases such as diarrhea, so that it can organize environmental health counseling, examination and intervention activities. Analyze environmental health counseling, examination and intervention activities/sanitarian. This research method is qualitative. There are environmental health actions, namely counseling that have not been carried out as has been implemented in the Regulation of the Minister of Health Number 13 of 2015, such as communicating with patients with the aim of identifying and overcoming environmental health problems. There is still a lack of communication between Sanitarian Officers and other Kalimas Health Center employees. Sanitarian Officers at the Kalimas Health Center are expected to be able to establish better coordination and communication, so that things do not happen that should be part of their duties as Health Workers, especially environmental health